2016
DOI: 10.1002/msc.1138
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Mobility in Axial Spondyloarthritis: A Cross‐Sectional Clinical Study

Abstract: Patients with USpA and AS had similar cervical and chest mobility, while thoracic and lumbar mobility were more severely restricted in AS. There were few gender differences in either subgroup. Further studies, to understand the full impact of USpA on spinal mobility, are needed. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…A recent cross-sectional study aiming to explore the differences regarding mobility in several subgroups of patients with axSpA concluded that gender might not have a major impact in the majority of BASMI components. 23 These findings are in accordance with the absence of gender-specific reference intervals for the definition of normal spinal mobility measures. 19 In another study performed with the DESIR cohort, HLA-B27 was associated with axial inflammation, less delay in diagnosis and decreased disease activity measured either by ASDAS-CRP or Bath Ankylosing Spondylitis Disease Activity Index.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…A recent cross-sectional study aiming to explore the differences regarding mobility in several subgroups of patients with axSpA concluded that gender might not have a major impact in the majority of BASMI components. 23 These findings are in accordance with the absence of gender-specific reference intervals for the definition of normal spinal mobility measures. 19 In another study performed with the DESIR cohort, HLA-B27 was associated with axial inflammation, less delay in diagnosis and decreased disease activity measured either by ASDAS-CRP or Bath Ankylosing Spondylitis Disease Activity Index.…”
Section: Discussionsupporting
confidence: 80%
“…However, disease duration may have a more significant impact on mobility in late disease. 23 Structural damage to the hips was independently associated with worse BASMI but not with maximal intermalleolar distance (non-significant association but numerically in the same direction as with BASMI). However, in the sensitivity analysis with purely axial sites, structural damage to the hips was also independently associated with worse maximal intermalleolar distance.…”
Section: Discussionmentioning
confidence: 85%
“…Thoracic and lumbar mobility is restricted in AS [29]. Larger tragus to wall distance shows worse spinal/upper cervical posture.…”
Section: Discussionmentioning
confidence: 99%
“…However, intermalleolar distance is included in the BASMI (22) and is therefore often reported as an outcome measure in studies with axSpA. Spinal mobility is known to be influenced by age (17,25,26), height (17,26), sex (25,26) and BMI (26) in the general population as well as in patients with axSpA (32)(33)(34)(35). In our population, patients with axSpA were younger, taller, more often men and had lower BMI than patients with other causes of chronic back pain, which may have influenced the results.…”
Section: Discussionmentioning
confidence: 99%